Tuning Electron‐Transfer Driving Force in Photosynthetic Special Pair Models - Ramirez Wierzbicki, Ivana Elizabeth (2024)
Visible-light excitation of a family of bimetallic ruthenium polypyridines with the formula [RuII(tpy)(bpy)(μ-CN)RuII(py)4L]n+ (RuRuLn+), where L=Cl-, NCS-, DMAP and ACN, was used to prepare photoinduced mixed-valence (PI-MV) MLCT states as models of the photosynthetic reaction center. Ultrafast transient absorption spectroscopy allowed to monitor photoinduced IVCT bands between 6000 and 11000 cm-1. Mulliken spin densities resulting from DFT and (TD)DFT computations revealed the modulation of the charge density distribution depending on the ligand substitution pattern. Results are consistent with PI-MV systems ranging from non-degenerate Class II to degenerate Class III or II/III, with electronic couplings between 1000 and 3500 cm-1. These findings guide the control electron localization-delocalization in charge-transfer/chargeseparated excited states, like those involved in the photosynthetic reaction center.